Importin-beta11 regulates synaptic phosphorylated mothers against decapentaplegic, and thereby influences synaptic development and function at the Drosophila neuromuscular junction. - Higashi-Kovtun, M.E.; Mosca, T.J.; Dickman, D.K.; Meinertzhagen, I.A.; Schwarz, T.L. (Journal of Neuroscience, 2010)
Importin proteins act both at the nuclear pore to promote substrate entry and in the cytosol during signal trafficking. Here, we describe mutations in the Drosophila gene importin-beta11, which has not previously been analyzed genetically. Mutants of importin-beta11 died as late pupae from neuronal defects, and neuronal importin-beta11 was present not only at nuclear pores but also in the cytosol and at synapses. Neurons lacking importin-beta11 were viable and properly differentiated but exhibited discrete defects. Synaptic transmission was defective in adult photoreceptors and at larval neuromuscular junctions (NMJs). Mutant photoreceptor axons formed grossly normal projections and synaptic terminals in the brain, but synaptic arbors on larval muscles were smaller while still containing appropriate synaptic components. Bone morphogenic protein (BMP) signaling was the apparent cause of the observed NMJ defects. Importin-beta11 interacted genetically with the BMP pathway, and at mutant synaptic boutons, a key component of this pathway, phosphorylated mothers against decapentaplegic (pMAD), was reduced. Neuronal expression of an importin-beta11 transgene rescued this phenotype as well as the other observed neuromuscular phenotypes. Despite the loss of synaptic pMAD, pMAD persisted in motor neuron nuclei, suggesting a specific impairment in the local function of pMAD. Restoring levels of pMAD to mutant terminals via expression of constitutively active type I BMP receptors or by reducing retrograde transport in motor neurons also restored synaptic strength and morphology. Thus, importin-beta11 function interacts with the BMP pathway to regulate a pool of pMAD that must be present at the presynapse for its proper development and function.